Valorization and bioremediation of digestate from anaerobic co-digestion of giant reed (Arundo donax L.) and cattle wastewater using microalgae. - SILVA, G. H. da (2024)
Anaerobic digestion followed by microalgal cultivation is considered a promising renewable alternative for the production of biomethane with reduced effluent generation, thus lowering the environmental impact. In this arrangement, in addition to generating energy, the microalgae act by potentiating the refinement of the effluents generated via anaerobic digestion (digestates). In this study, the microalga Tetradesmus obliquus was cultivated in photobioreactors with the final digestate resulting from the co-digestion of Arundo donax L. plant biomass and cattle wastewater. The biotechnological route used was efficient, and the biogas production ranged from 50.20 to 94.69 mL gVS−1 . The first-order kinetic model with variable dependence (FOMT) provided the best fit for the biogas production data. In the microalgal post-treatment, the removal values ranged from 81.5 to 93.8% for the chemical oxygen demand, 92.0 to 95.3% for NH4 + -N, and 41.7 to 83.3% for PO4 3− after 26 days. The macromolecular composition of the algal biomass reached lipid contents ranging from 33.4 to 42.7%. Thus, the proposed process mediated by microalgae can be considered promising for the bioremediation and recovery of effluents produced by agriculture through the use of microalgal biomass for bioproduct production.